A multicentre prospective randomized equivalence trial of a soft bandage and immediate discharge versus current treatment with rigid immobilization for torus fractures of the distal radius in children: Protocdol for the forearm fracture recovery in children evaluation (force) trial. (June 2020) - Achten, J.; Knight, R.; Dutton, S. J.; Costa, M. L.; Mason, J.; Dritsaki, M.; Appelbe, D.; Messahel, S.; Roland, D.; Widnall, J.; Perry, D. C.
No abstract available